Pupillometry in the Emergency Department: A Tool for Predicting Patient Disposition - Hector Gonzalez Jr.; Yanying Chen; Newton Addo; Debbie Y. Madhok (Western Journal of Emergency Medicine)
Introduction: The ability to accurately assess and predict the disposition of comatose patients from within the emergency department (ED) remains a critical challenge. Traditional methods lack precision and consistency. Our goal was to evaluate the prognostic capability of the neurological pupil index (NPI) in predicting patient disposition from within the ED. Method: This prospective observational study followed 50 comatose patients (Glasgow Coma Scale [GSC] score < 9) who were enrolled via convenience sampling and subsequently treated in the ED at a Level 1 trauma center and public safety-net hospital in San Francisco, CA. We calculated NPI scores and collected data on patient demographics, clinical characteristics, and outcomes. The NPI scores were categorized into three groups: 0 (very poor); 0.1–3.0 (poor to moderate); and 3.1–5.0 (good). We used ANOVA, the Pearson chi-squared test, Wilcoxon rank-sum test, and Fisher exact test to assess the association between NPI scores and discharge status. Results were reported as odds ratios with 95% confidence intervals, with a P-value < .05 considered statistically significant. Results: The median age of patients in this study was 58 years (IQR 42–74), and 66% were male. Higher NPI scores (five-point scale with 3.1–5.0 considered normal) were significantly associated with an increased likelihood of ED discharge (82%), , while lower NPI scores (0, nonreactive pupil) were predominantly associated with hospital admission (92%) (P < .001). Significant predictors of discharge status included patient age, GCS scores, and coma etiology. Conclusion: This study highlights the utility of the NPI in predicting patient disposition from within the ED. Higher NPI scores were strongly associated with an increased likelihood of ED discharge. These findings support the idea that NPI has the potential to enhance the accuracy of prognostic assessments, in comparison to subjective characterizations of pupil activity. Additional research with larger, multicenter cohorts are needed to confirm these results and establish standardized protocols for integration of NPI in ED workflow.